Survivable WDM mesh networks. Part I-Protection - Ramamurthy, S.; Mukherjee, B. (IEEE INFOCOM '99. Conference on Computer Communications. Proceedings. Eighteenth Annual Joint Conference of the IEEE Computer and Communications Societies. The Future is Now (Cat. No.99CH36320), 1999)
This investigation considers optical networks which employ wavelength cross-connects that enable the establishment of wavelength-division-multiplexed (WDM) channels, between node-pairs. In such and other networks, the failure of a network element (e.g., fiber link, cross-connect, etc.) may cause the failure of several optical channels, thereby leading to large data losses. This study examines different approaches to protect mesh based WDM optical networks from single-link failures. These approaches are based on two basic survivability paradigms: (a) path protection/restoration, and (b) link protection/restoration. In path- and link-protection schemes, backup paths and wavelengths are reserved in advance at the time of call setup. Path- and link-restoration schemes are dynamic schemes in which backup paths are discovered (from the spare capacity in the network) upon the occurrence of a failure. In part 1 of this study presented in this paper, we formulated integer linear programs to determine the capacity requirements for the above protection schemes for a static traffic demand.